If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(8n + -6) = 27 + 9n Reorder the terms: 2(-6 + 8n) = 27 + 9n (-6 * 2 + 8n * 2) = 27 + 9n (-12 + 16n) = 27 + 9n Solving -12 + 16n = 27 + 9n Solving for variable 'n'. Move all terms containing n to the left, all other terms to the right. Add '-9n' to each side of the equation. -12 + 16n + -9n = 27 + 9n + -9n Combine like terms: 16n + -9n = 7n -12 + 7n = 27 + 9n + -9n Combine like terms: 9n + -9n = 0 -12 + 7n = 27 + 0 -12 + 7n = 27 Add '12' to each side of the equation. -12 + 12 + 7n = 27 + 12 Combine like terms: -12 + 12 = 0 0 + 7n = 27 + 12 7n = 27 + 12 Combine like terms: 27 + 12 = 39 7n = 39 Divide each side by '7'. n = 5.571428571 Simplifying n = 5.571428571
| 3/2x-14/4=-73/4 | | 4x-1/2=x=7 | | 5(2+x)+0=10 | | (7x^4x^5)/7x^7y(x^2y)^4 | | 5(2+x)+10=2 | | 5(y+5)+4=25 | | -5(t-2)-(t+2)=3 | | 3a-2=5a-18 | | 5(2s+15)=10(s+1)-12s | | M=2TH+2TA | | 10(2+x)+5=2 | | 10(2+x)+5=0 | | 10(2+x)+0=5 | | 7x4/6 | | 5+8(x-5)=2-2(x-2) | | 10m+70=10m+10-16m | | 10(2+x)+0=6 | | -3(r+2)=-15 | | 2w+10=60 | | 2n+1+n=-8 | | W/5=24-4 | | X-13-2x=2 | | 2x^3+12x^2+16x=y | | 18p+q+3p+12q= | | x+78=72 | | 3(5x-8)-6x+20=-22 | | X+99=93 | | 4(3r-4)=3(r+9)+2 | | b-1/2=2 | | 3(Y+9)+3Y=30 | | 10+6a=-104 | | f(x)=3x^2+5x+7 |